Cultural Statuses of Urban Women in Duhok City: An Analytic Study - Samya Saeed Khalid; Muhammad Saeed Husein Ahmad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The study aimed to analyze the cultural Statuses of urban women in the city of Duhok, as the role of urban women has changed after their involvement in the fields of education and work, which helped them to overcome the stereotypical roles that were surrounded socially and culturally in society, these stereotypical roles prevented them from proving themselves according to their emotional, spiritual and mental needs and forced women to employ their intellectual energies in the field of domestic function and traditional biological roles in the fields of reproduction and domestic work, but urban sprawl imposed itself on various patterns of Social life contributed to pushing women to the field of education, which gained women economic independence that led to the development of their social status by meeting their personal needs and contributing to meeting and satisfying family needs. But women's activities in freedom from social and cultural restrictions did not create that change in the cultural conditions of women despite the manifestations of urbanization in the material aspect of modern life in society, and the study found that the statuses of women are still characterized by a lot of negativity and stereotypes that do not look at women only from the standpoint of the housewife and responsible for reproduction, and despite the multiplicity of roles and social - cultural functions after going out to work, they still face obstacles in their environment, and policies, Women's socialism is still unable to reduce the gender gap, and manifestations of equality do not exceed some superficial aspects of women's urban life in the community of Duhok.